USING SHEEP FACIAL GRIMACE SCALE, INFRARED THERMOGRAPHY AND CORTISOL HORMONE TO MEASURE PAIN IN SHEEP INFECTED WITH MASTITIS DISEASE - Hussein, Nizar J.; Al-Naqshabendy, Assel A. (Science Journal of University of Zakho, 2024)
The purpose of this study was to apply sheep pain facial expression scales (SPFES) to sheep infected with mastitis, measuring peripheral temperatures and serum cortisol hormone. Twenty-three healthy ewes and 23 infected ewes with clinical mastitis were included in this research from January 2022 to April 2023. Images were taken from each ewe to detect facial grimace scales of ewes. Nasal, eye and ear temperatures were collected using infrared thermal imaging camera. Moreover, serum cortisol hormone was collected from the blood. It was found that there was a significant decrease (p
Keywords: Facial Expressions; Pain Measurement; Peripheral Temperatures; Cortisol